Antimicrobial stewardship in South Africa: a scoping review of the published literature. Issue 3 (28th November 2019) - Chetty, Sarentha; Reddy, Millidhashni; Ramsamy, Yogandree; Naidoo, Anushka; Essack, Sabiha
Abstract: Objectives: To map published data of antimicrobial stewardship (AMS) interventions that are currently being carried out in hospitals and clinics in the public and private health sectors of South Africa in line with the antimicrobial resistance (AMR) strategy of South Africa. Methods: A systematic scoping review was conducted to identify AMS initiatives in the public and private health sectors of South Africa for the period 1 January 2000 to 31 March 2019. An electronic search of databases was made including PubMed, Scopus, a key medical journal ( South African Medical Journal ), University of KwaZulu-Natal (UKZN) WorldCat iCatalogue and AMR networks: Federation of Infectious Diseases Societies in South Africa (FIDSSA). Reference lists of published articles were also reviewed for inclusion. Keywords included 'antimicrobial antibiotic stewardship South Africa'. Findings: Of a total of 411 articles, using a stepwise screening process, 18 articles were selected for inclusion in the review. The interventions/initiatives were divided into four broad categories: (i) AMS intervention: prescription audits and usage; (ii) AMS intervention: education and its impact; (iii) other AMS interventions; and (iv) the role of different healthcare professionals in AMS. Conclusions: The data identifies a need for and the value of AMS in both the public and private health sectors of South Africa. Initiatives are carried out across both sectors but more attention needs to be focused on AMS implementation in line with the National AMR Strategy of South Africa. Collaboration between the different sectors will aid in overcoming the AMR challenge.